Orientations and Branches of Moire Waves in Three-dimensional Displays - Saveljev, Vladimir (KOREAN PHYSICAL SOC, 2010)
Theoretical and experimental investigations of the orientation of moire waves in three-dimensional displays are performed. We propose using the polar forms which appear to be convenient in describing moire patterns near minimization point. The presence of two branches for each wave and switching between them is confirmed experimentally. The experimental and theoretical data are in good agreement, except in the close neighborhood of the minimization point.
Keywords: REDUCTION; PATTERNS